Enhanced thermoelectric performance of SnSe by controlled vacancy population - Lee, Ji-Eun; Kim, Kyoo; Nguyen, Van Quang; Hwang, Jinwoong; Denlinger, Jonathan D.; Min, Byung Il; Cho, Sunglae; Ryu, Hyejin; Hwang, Choongyu; Mo, Sung-Kwan (Springer | Korea Nano Technology Research Society, 2023)
The thermoelectric performance of SnSe strongly depends on its low-energy electron band structure that provides high density of states in a narrow energy window due to the multi-valley valence band maximum (VBM). Angle-resolved photoemission spectroscopy measurements, in conjunction with first-principles calculations, reveal that the binding energy of the VBM of SnSe is tuned by the population of Sn vacancy, which is determined by the cooling rate during the sample growth. The VBM shift follows precisely the behavior of the thermoelectric power factor, while the effective mass is barely modified upon changing the population of Sn vacancies. These findings indicate that the low-energy electron band structure is closely correlated with the high thermoelectric performance of hole-doped SnSe, providing a viable route toward engineering the intrinsic defect-induced thermoelectric performance via the sample growth condition without an additional ex-situ process.